1986
DOI: 10.1152/jappl.1986.61.5.1882
|View full text |Cite
|
Sign up to set email alerts
|

Effect of posture on vital capacity

Abstract: The influence of some extreme body postures on vital capacity (VC) was examined in young adult humans. Two postures required full support of body weight by the arms: arms up, hanging from a bar, and arms down with hands gripping parallel bars. Three involved muscles that flex and extend the trunk: a partial sit-up position while supine and nearly maximal spinal extension and flexion while standing. Changes at the inspiratory and expiratory volume extremes were recognized by having the subjects do two VC effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Our study supports this suggestion. Haas et al 13 and Appel et al 14 reported that altering the orientation of accessory muscles of respiration (as seen in FSP) has marked effects on the operating length and function of the diaphragm. Although we could not evaluate the effect of FSP on the operating length of the diaphragm, it is reasonable to assume that some alteration may occur.…”
Section: Discussionmentioning
confidence: 99%
“…Our study supports this suggestion. Haas et al 13 and Appel et al 14 reported that altering the orientation of accessory muscles of respiration (as seen in FSP) has marked effects on the operating length and function of the diaphragm. Although we could not evaluate the effect of FSP on the operating length of the diaphragm, it is reasonable to assume that some alteration may occur.…”
Section: Discussionmentioning
confidence: 99%
“…TLC and RV are relatively insensitive to subjects′ orientation in gravity, because gravitational forces are small in relation to the larger forces of muscles and elastic recoil that operate at the volume extremes. TLC and RV are also remarkably insensitive to body posture and use of the limbs [7].…”
Section: Discussionmentioning
confidence: 99%
“…Body position can influence respiratory function 1 , 2 ) . Changes in body position can alter the length of a respiratory muscle, namely the diaphragm, thereby influencing its ability to generate tension 3 ) .…”
Section: Introductionmentioning
confidence: 99%